Wellbeing Evidence for the Assessment of Progress - Paul Anand; Laurence Roope; Andreas Peichl (Institute for the Study of Labor (IZA), 2016)
In recent years considerable interest has developed in going 'beyond GDP' to develop measures of economic progress which are more explicitly based on human wellbeing. This work has been inspired, in part, by Sen's non-utilitarian approach to welfare economics, but has been constrained by a lack of empirical indicators relating to human potential. In this paper, therefore, we develop a framework for understanding wellbeing, drawing closely on Sen's seminal contributions to welfare economics, as well as the economic literature on life satisfaction, and use it to generate novel data for the USA and UK consistent with all the components of the theory. We use these data to illustrate some of the life quality analyses that might follow. Specifically, we investigate how various indicators of capability are distributed by ethnicity and gender, and compare and contrast the types of capability which appear relatively strong/weak within each country. In addition, we consider the extent to which life satisfaction and daily activities depend on resources and non-cognitive skills. The paper concludes that with an expansion of the scope of routinely collected survey data, it is feasible to empirically implement fully Sen's theory to provide a much richer account of the wellbeing outcomes that derive from economic progress than is currently the case.
Keywords: D60; I31; 330; wellbeing; stochastic dominance; life satisfaction; Sen